DOI: 10.32657/10220/47652
|View full text |Cite
|
Sign up to set email alerts
|

Bias temperature instability study on switching defects in SiON and high-K gate dielectrics

Abstract: provided the initial project direction, gave suggestions in the interpretation of the measurement data, and edited the manuscript.  Dr. A. A. Boo collected the measured threshold voltage shift, analyzed the data collected and drafted the manuscript.  I collected the measured gate current shift (stress-induced leakage current, SILC), analyzed the data collected and assisted in drafting the manuscript. Chapter 4, Section 4.3 is published as Z. Y. Tung and D. S. Ang, "Transient to temporarily permanent and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 170 publications
(404 reference statements)
0
8
0
Order By: Relevance
“…This type of relation between PV flux and form drag is not new. For isentropic surfaces uninterrupted by the earth's surface, Tung (1986) showed that…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of relation between PV flux and form drag is not new. For isentropic surfaces uninterrupted by the earth's surface, Tung (1986) showed that…”
Section: Resultsmentioning
confidence: 99%
“…assuming only hydrostatic balance in the vertical), it is more insightful from a dynamical point of view to use potential temperature, θ, as the vertical coordinate because, under adiabatic inviscid conditions, air flows along isentropic surfaces while conserving Ertel potential vorticity (PV). In isentropic zonal average formalism, the midlatitude circulation is also direct and is driven by eddy transport of PV (Tung 1986). The analogy between general circulation in θ-coordinate PE atmospheres and that in QG atmospheres is evident and useful.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was adopted by Duffy (1978) to study the instability of the most unstable Eady mode in the limit of zero shear, and by Lorenz (1972) for barotropic Rossby waves. The matter of convergence of spectral series was discussed by Tung (1976). Given the spectra obtained in the previous section, we feel safe in retaining zonal wave numbers 0 and k E only.…”
Section: Dispersion Relation For Modementioning
confidence: 94%
“…Following Matsuno's work more sophisticated models have been formulated to include the effects of spatially variable model parameters (e.g. static stability, Newtonian cooling and Rayleigh friction) while the likely importance of interannual differences in both winds and forcing has been remarked on (Schoeberl and Geller 1977 -corrected by Schoeberl, Geller and Avery 1979;Simmons 1974;Tung 1976). Models of this type have also been applied to possible effects of the stratospheric circulation upon long waves in the troposphere (Bates 1977), and hence the possible influence of variations in solar activity upon the troposphere (Geller and Alpert 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Because of limitations of the data base, for example, Matsuno (1970) had to use a stratospheric wind field based upon climatology rather than a specific period, and forcing and verification data for different periods (cf. Tung 1976). Here we have used analyses of data from the Stratospheric Sounding Unit on board NOAA-6 to provide both the model input values and consistent verification.…”
Section: Introductionmentioning
confidence: 99%